D1 versus D2 lymphadenectomy for gastric cancer. Issue 3 (18th April 2012) - Schmidt, Benjamin; Yoon, Sam S.
Abstract Significant variability exists throughout the world in the extent of lymphadenectomy that is performed for gastric adenocarcinoma. D2 lymphadenectomy is the standard lymphadenectomy performed in high incidence countries such as Japan and South Korea, and less extensive lymphadenectomies are often performed in lower incidence countries such as the Unites States. This article reviews the evidence on the extent of lymphadenectomy that should be performed for gastric adenocarcinoma. J. Surg. Oncol. 2013;107:259–264. © 2012 Wiley Periodicals, Inc.